Die DDR-Literatur und die Wissenschaften - Gencarelli, Angela (Studien und Texte zur Sozialgeschichte der Literatur, 2022)
What is the relationship between literature and the sciences? What scientific insights has it adopted and which knowledge has it produced in the process? These are the kinds of research questions that this volume is the first to discuss in relation to the previously neglected field of GDR literature, which had a productive, critical relationship to the societally central "productive power of science," which was seen as "revolutionary."